Fabrication of composite magnetic HAP/GO-PES membrane for iron removal - Roslan, Luqman (2018)
Polymeric based membrane usually having problems with fouling and hydrophilicity. Thus, a new material is introduced which is graphene oxide (GO). GO is the materials that have a unique properties and hydrophilic nature. Besides, GO can help to enhance the permeate flux, improve mechanical strength, increase surface hydrophilicity, and reduce fouling. GO has good hydrophilicity compared to graphite due to presence of oxygenous group carbonyl, epoxide, hydroxyl and carboxyl. GO is synthesise from the modified Hummers method. GO then is further bind to the polymeric membrane surface. The magnetic NPs and hydroxyapatite (HAP) was added into the GO-PES membrane to form GO-MHAP-PES membrane. The membranes are fabricated using the phase inversion technique and embedded with various percentages of GO-MHAP (0.5wt%, 1.0wt%, 1.5wt% and 2.0wt%). Last but not least, morphology and performance test was investigated using X-ray diffraction (XRD), water contact angle, and Fourier Transform infrared (FTIR). Conclusion of the experiment stated that the modified fabricated membrane GO-MHAP-PES membranes have a low water contact angle stated at 60.73º, 58.03º, 57.73º, and 58.2º lower than GO-PES membrane at 68.2º. The results show that, addition of GO will improved it affinity toward water than a typical PES membrane. In addition, GOMHAP-PES membranes also show a good rejection rate for iron removal. The iron removal is at 96.5% and 97.9% demonstrated by GO-MHAP-PES 1.5wt% and GOMHAP-PES 2.0wt%.